Rancang Bangun Website Sekolah Pada SMK Negeri 1 Oku Selatan Menggunakan Php & Mysql Sebagai Sarana Informasi - Dian Sri Agustina; Yunita Trimarsiah; Satria Novari (Elkom: Jurnal Elektronika dan Komputer, 2024)
Website is an existing facility on the internet, and is one of the alternative means of information and promotional media used to get new news. The purpose of making the site of SMK Negeri 1 OKU Selatan is to assist in promoting and informing the School so that it is easy to access by all people wherever they are. Therefore this study took the initiative to Build a School Website at SMK NEGERI 1 OKU SELATAN using PHP & MYSQL as a means of promotion and information. The research subjects in this thesis are South OKU 1 Public Vocational School The software used in making South Oku 1 South Vocational School website is Adobe Photoshop CS3, XAMPP, PHP, Sublime Text and MySQL. The result of this final project is a website for SMK Negeri 1 Oku Selatan, the website was developed using PHP and MySQL. The contents contained in the website are in the form of information about agencies such as: profile, department, gallery and contact that can be contacted at the SMK NEGERI 1 OKU SELATAN institution.